Probing structural integrity of single walled carbon nanotubes by dynamic and static compression. Issue 11 (10th September 2014) - Noël, Maxime; Ananev, Sergey; Mases, Mattias; Devaux, Xavier; Lee, Juhan; Evdokimov, Ivan; Dossot, Manuel; McRae, Edward; Soldatov, Alexander V.
<x xml:space="preserve">Abstract</x> We report on a first study of single walled carbon nanotubes (SWCNTs) after application of dynamic (shock) compression. The experiments were conducted at 19 GPa and 36 GPa in a recovery assembly. For comparison, an experiment at a static pressure of 36 GPa was performed on the material from the same batch in a diamond anvil cell (DAC). After the high pressure treatment the samples were characterized by Raman spectroscopy and transmission electron microscopy (TEM). After exposure to 19 GPa of shock compression the CNT material exhibited substantial structural damage such as CNT wall disruption, opening of the tube along its axis ("unzipping") and tube shortening ("cutting"). Dynamic compression to 36 GPa resulted in essentially complete CNT destruction whereas at least a fraction of the nanotubes was recovered after 36 GPa of static compression though severely damaged. The results of these shock wave experiments underline the prospect of using SWCNTs as reinforcing units in material WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim)